Ekspansi Islam dan Kebijakan Pemerintahan pada Masa Khalifah Umar bin Khattab - Enur Nurjanah; Eneng Dewi Siti Sobariah (Progam Studi Sejarah Peradaban Islam (SPI), Fakultas Ushuluddin Adab dan Humaniora, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
This article describes the time of the caliph Umar bin Khatab in the expansion and spread of Islam outside the Arabian peninsula, as well as the policies taken during his reign. Based on literature studies from various books on the history of Islamic civilization and the journal History of Islamic Civilization, especially those discussing the Caliph Umar bin Khattab, it was found that there was a very rapid expansion of Islam during the time Umar bin Khattab served as caliph. The results of this research first found that the Islamic expansion carried out by Umar expanded not only in the Arabian peninsula, but also extended to various regions such as Damascus, Ajnadain, Palestine, Egypt, Iraq, Persia, Syria, and Nahawand. This expansion is28 very beneficial for Muslims, namely for the development of Islam, as well as upholding Islamic politics and upholding Islamic law. Second, the policies carried out by Umar were ijtihad policies and political policies. Ijtihad policy by changing systems that do not yet exist in the Koran, as well as improving regulations that need to be revised or changed based on the needs and developments of the times. While the political policy is to renew the government structure and state administration structure.